Difference in tar reforming activities between biochar catalysts activated in H2O and CO2. (1st July 2020) - Liu, Yurong; Paskevicius, Mark; Wang, Hongqi; Fushimi, Chihiro; Parkinson, Gordon; Li, Chun-Zhu
Highlights: H2 O-activated biochar has higher catalytic activity than CO2 -activated biochar. H2 O-activated biochar has higher content of O-containing groups than that of CO2 -activated biochar. Addition of excess H2 O during tar reforming can produce additional O-containing groups. Abstract: This study investigates the difference in the activities between biochar catalysts activated in H2 O and CO2 for in situ tar reforming. The experiments were performed in a two-stage fluidized-bed/fixed-bed at 800 °C. Mallee wood biochar (106–250 μm) was activated in pure CO2 or 15 vol% H2 O balanced with Ar (15 vol. %H2 O/Ar) for different times (0–50 mins) before being used as a catalyst for tar reforming. Based on the analysis of tar samples, it was found that H2 O-activated biochar showed higher catalytic activity than CO2 -activated biochar in both steam reforming and dry reforming of tar. Moreover, under otherwise identical conditions, reforming in steam was always more rapid than that in CO2 regardless of the atmosphere in which biochar was activated. The characterisation of biochar showed that H2 O activation resulted in a biochar with a higher content of O-containing functional groups and aromatic C-O structures than that from CO2 activation. In addition, the content of O-containing functional groups and aromatic C-O structures of biochar after the steam reforming were higher than those after the dry reforming of tar. The different catalytic activities between the biochars activated by H2 O and CO2 could be attributed to the different amounts of O-containing functional groups and aromatic C-O structures in biochar generated by H2 O or CO2 activation. An extra supply of H2 O plays an important role in improving and maintaining the catalytic activity of biochar during tar reforming.